2022
DOI: 10.1111/ajad.13266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of state and trait anxiety severity on retention and phase advancement in an outpatient buprenorphine treatment program

Abstract: Background and Objectives: Comorbid anxiety is common among buprenorphine patients and may lead to poorer outcomes. This study aimed to examine the prevalence and impact of anxiety severity, measured by the State-Trait Anxiety Inventory (STAI) form Y-1 & Y2 scale, on treatment outcomes (retention and phase advancement) among outpatient buprenorphine-treated patients. Methods: A retrospective chart review of 94 patients admitted to an outpatient buprenorphine treatment program was conducted. Patients were dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have not found any association between baseline anxiety and OAT retention. 46 48 Therefore, several factors might explain our results. Firstly, baseline anxiety alone may be irrelevant to overall treatment retention and guiding OAT selection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have not found any association between baseline anxiety and OAT retention. 46 48 Therefore, several factors might explain our results. Firstly, baseline anxiety alone may be irrelevant to overall treatment retention and guiding OAT selection.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, 1 study suggested distinguishing between state anxiety and trait anxiety to contextualize our findings, given that the BAI is a state-based measure of anxiety. 48 State anxiety represents transient anxious reactions to specific adverse situations at specific moments, while trait anxiety describes individual differences related to a tendency to present in an anxious state. 48 Ultimately, this distinction could help to understand our findings better, given that our measure of baseline anxiety may capture participants’ transient anxiety at the time of evaluation, which could have resulted from various aetiologies such as high rates of unstable housing, opioid withdrawal, and chronic pain.…”
Section: Discussionmentioning
confidence: 99%